The Implementation of Brainstorming Method using an Investigation Group Model to Improve the Activeness and Learning Result - Astuti, yuni Tri; Haryono, Agung (Classroom Action Research Journal (CARJO), 2018)
The purpose of this research is to gain information about the implementation of brainstorming method in group investigation model on the Economic subject and also to know the improvement of activity and the student’s study outcome of grade X Social 3 Senior High School 1 Batu. The observation becomes a method of collecting data, while the exercises or test given to the students and fields notes, all of those items analyzed later using the qualitative technique. The outcomes of this research are: (1) the improvement of student activity around 18.71% from the first cycle to the second cycle, namely 63.30% in the first cycle and 82.31% in the second cycle; (2) the improvement of student activity around 22.22% from the first cycle to the second cycle, which is signed by the increasing number of student which passed the bottom line of score around 70.37% in the first cycle and 92.59% in the second cycle. The implementation of brainstorming method in group investigation model planned can be used as an alternative learning process model on an economic subject that can build the interest of the students on this subject.